2009
DOI: 10.1111/j.1474-9726.2009.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16INK4a in peripheral blood T‐cells is a biomarker of human aging

Abstract: Summary Expression of the p16INK4a tumor suppressor sharply increases with age in most mammalian tissues, and contributes to an age-induced functional decline of certain self-renewing compartments. did not independently correlate with gender or bodymass index, but was significantly associated with tobacco use and physical inactivity. In addition, p16 INK4a expression was associated with plasma interleukin-6 concentration, a marker of human frailty. These data suggest that p16 INK4a expression in PBTL is an eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
419
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 423 publications
(448 citation statements)
references
References 58 publications
21
419
4
4
Order By: Relevance
“…Studies have shown that the number of senescent cells increases with aging in multiple human tissues, including circulating T cells (Liu et al., 2009). Senescent cells are characterized by senescence‐associated secretory phenotype (SASP) that release inflammatory mediators, proteinases and other molecules in the surrounding niche, from where they are eventually released into circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the number of senescent cells increases with aging in multiple human tissues, including circulating T cells (Liu et al., 2009). Senescent cells are characterized by senescence‐associated secretory phenotype (SASP) that release inflammatory mediators, proteinases and other molecules in the surrounding niche, from where they are eventually released into circulation.…”
Section: Resultsmentioning
confidence: 99%
“…This has allowed p16 INK4a expression to serve as a biomarker of molecular aging, which can be used to measure the senescence burden and predict cellular function in some settings (Koppelstaetter et al., 2008; Liu et al., 2009; Wood et al., 2016). To determine this relationship in primary human chondrocytes, we analyzed whether the expression of p16 INK4a was associated with markers of chondrocyte dysfunction independent of chronological aging (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The quantity of this subset increases during aging (thus the correlation of p16 INK4a to age) and p16 INK4a also serves as a biomarker that identifies chondrocytes with greater potential for secreting factors that drive tissue dysfunction (thus the correlation of p16 INK4a to SASP markers). The utility of p16 INK4a as a biomarker of molecular age in other cell types has been demonstrated by assessing the impact of lifestyle modifications such as smoking or exercise (Liu et al., 2009), predicting the risk for particular negative outcomes after chemotherapy (Demaria et al., 2017), and screening the quality of potential donor organs (Koppelstaetter et al., 2008). For chondrocytes, screening patients for low p16 INK4a expression may improve the outcomes of autologous chondrocyte implantation procedures, as the success of this procedure requires avoidance of senescence to ensure sufficient expansion and subsequent re‐differentiation of the chondrocytes (Ashraf et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of effect of p16 deletion cannot be attributed to compensation by Arf, because HSCs from irradiated Arf and p16/Arf KO mice exhibited changes similar to those seen in the cells from WT mice after TBI. The finding that IR induced HSC senescence and residual BM suppression in a p16 and Arf-independent manner is intriguing, because upregulation of p16 and Arf has been implicated in mediating induction of HSC senescence in a variety of pathological conditions and during aging, 8,41,42 and it has been shown that IR induced senescence in BM stromal cells in a p16-and Arf-dependent manner. 32 Furthermore, early T-lymphoid progenitors are exquisitely dependent on CDK4/6 activity and, therefore, are very sensitive to p16 upregulation for induction of senescence during aging.…”
Section: Discussionmentioning
confidence: 99%